A Systematic Review Demonstrates How Surrogate Populations Help Inform Conservation and Management of an Endangered Species—The Case of Cook Inlet, Alaska Belugas - Norman, Stephanie A.; Dreiss, Lindsay M.; Niederman, Talia E.; Nalven, Katharine B. (Frontiers in Marine Science, 2022)
The genetically and geographically isolated Cook Inlet beluga whale (CIB) was listed as endangered under the Endangered Species Act in 2008 and a federal recovery plan was adopted in 2016. Despite these measures, the population has failed to make demonstrable progress toward recovery. Data and knowledge gaps exist, as well as high uncertainty in the recovery plan, regarding the impact and severity of identified threats on CIB health and recovery, particularly for threats driven by anthropogenic factors, and cumulative effects. These data deficiencies may hinder threat prioritization and conservation and management actions. Odontocete populations in similarly ecologically precarious situations may serve as research surrogates to help fill information gaps and guide future CIB research and conservation. Through a systematic review of CIB and selected surrogate species [St. Lawrence beluga (SLB), Hector’s dolphins (HD), and southern resident killer whales (SRKW)], we identify gaps associated with threats described and ranked in the CIB recovery plan. All threats identified by the National Marine Fisheries Services as “high”-concern to CIB recovery, except noise, are lower in publication volume compared to publications related to high concern threats in SLB and SRKW. “Medium” or “low” threats to CIB, such as prey reduction and contaminants, respectively, are identified as higher priority threats in surrogate populations. These topics have been more heavily researched for surrogates and suggests that synthesis of this work may help reduce uncertainty, to aid in informing management actions for CIB. Specifically, publishing volume suggests SLB and SRKW are valuable surrogates for understanding the impacts of noise, prey, and contaminants. Publishing volume is necessary to choose a surrogate, but is not sufficient. Surrogates were chosen based on physiological similarities to CIB as well as their comparable management situations. Therefore, these lower-ranked threats should be ranked more highly and researched specifically in regard to CIB. We use this review to offer management recommendations based on current CIB and surrogate literature regarding listed threats in the CIB recovery plan. Our analyses suggest that CIB may benefit from a revision to and elevation of some low and medium-concern threats such as contaminants, habitat degradation, and prey reduction.